Synthesis and comparative photoluminescence of CdZnSe / ZnS and CdZnSe / ZnSeS alloy quantum dots - Yen, Nguyen Hai; Hai, Nguyen Ngoc; Vu, Le Van; Dung, Phan Tien; Nghia, Nguyen Xuan; Coolen, Laurent; Nga, Pham Thu (Vietnam Journal of Science and Technology, 2014)
In order to search for new structures and compositions of quantum dots, suppress the blinking photoluminescence (random changes between high emission state ( on) and low emission status ( off ) under continuous photo- excitation ) and serve the application purposes in bio- medical and in optoelectronic devices , we have studied the fabrication of new alloy quantum dots ( QDs ). In this paper, we present new results on alloy core / shell quantum dots, with changed alloy shell composition, that was CdZnSe/ZnSexS1-x a ML with x ( x = 0 , 0.2, 0.4, 0.5 , 0.6, 0.8) and the shell thickness in monolayer (ML) ( a = 2 , 4 , 6 ) . The emission spectra and the intensity change according to the composition of the alloy shell. The full width a half maximum ( FWHM ) of the emission spectra of quantum dots CdZnSe is 25.5 nm. Covered with a shell layer, the emission intensity of the CdZnSe core increases along with the shell thickness. For comparison purpose, two different shell materials have been used, which are ZnS and ZnSeS alloy. With the same shell thickness, the emission wavelengths and intensity of the QDs change when the shell’s composition changes.The photoluminescence (PL) decay and the PL blinking of the alloy QDs was studied. It was shown that the alloy QDs spent by the nanocrystal in the ON state ranged typically between 20 and 40 %, and was dependent on the core composition. Detailed discussions on the experiment results are presented.